Rancang Bangun Sistem Informasi Penggajian Ketua Rukun Tetangga di Kantor Kelurahan Sugihan Sukoharjo - Susilowati Susilowati; Chairullah Naury; Ari Pantjarani (Indonesian Journal of Information Technology and Computing (IMAGING), 2025)
Human Resources Management has the responsibility of managing the payroll system. The function of the payroll system is to provide compensation to workers in the form of salaries in exchange for contributions from an institution. The payroll data processing process requires a high level of accuracy to avoid errors, so that it can produce accurate salary calculations. The current process of managing payroll data for the Head of Neighborhood Units (RT) in the Sugihan Sukoharjo sub-district still uses manual methods, this causes the presentation of payroll reports to not be able to run quickly because it requires high accuracy. Delays in presenting payroll reports do not rule out the possibility of delays in salary payments. To anticipate this, the RT Head's salary system at the Sugihan Sukoharjo Village Subdistrict Office needs to be supported by a computerized information system. In order to develop a payroll information system for RT Heads at the Sugihan Sukoharjo Village Subdistrict Office, researchers designed a website-based payroll information system using the Native PHP programming language and MySQL database. The researcher presents the design of this payroll information system in the form of scientific research published in research journal format. The aim of designing this website-based payroll information system is to provide convenience for the Human Resources Management section at the Sugihan Sukoharjo Village Office in managing the RT Head's payroll data, so that the presentation of payroll reports becomes faster. Keywords: design, information system, payroll, mysql, php